Resignation of Instructing Doctors in the Teaching Hospital of the Collaborative Project to Increase Rural Doctors, Ministry of Public Health - ภู่รัก, สุกิจ; สุขุมาลไพบูลย์, พิมพ์เพชร; เตชะเคหะกิจ, วิน (Journal of Health Science of Thailand, 2023)
As instructing doctors have long had an important role in both assisting medical care services and teaching medical students in the teaching hospitals affiliating with the Collaborative Project to Increase Rural Doctor (CPIRD). However, the resignation of the instructing doctors before completing a 3-year course remains problematic in the system. This study aimed to explores the resignation of instructing doctors in teaching hospitals. A retrospective study was conducted using administrative data from the Personnel Administration Division, Ministry of Public Health, to identify instructing doctors who were registered in the teaching hospitals during 2015-2018. Information about gender, regions of workplace, hospital sizes, and worked departments, were collected. A Poisson regression analysis was performed to find the association of covariates with physician resignation. A total of 1,076 instructing doctors was identified, with 142 (13.2%) resigned before completing the course. The results demonstrated that instructing doctors who worked in small or medium-sized hospitals were 1.98 (95%CI=1.35-2.90) and 1.58 (95%CI=1.07-2.34) times more likely to resign in comparison with those who worked in large teaching hospitals, respectively. Moreover, physicians who worked in the OB-GYN department had 1.71 times (95%CI=1.05-2.80) higher chance of resignation, compared with their peers in internal medicine. This study found no statistically significant difference between sex and region of working place with the resignation of instructing doctors. This study sheds light on the impact of working environment on the physicians’ decision to resign, presented in terms of hospital sizes and worked departments. Working environments in large-sized teaching hospitals may help instructing doctors to built and strengthened self-confidence in medical practice. Supervision and coaching can ensure their capabilities and competences for being a clinician and an instructing doctor. Results from this study can inform policymakers about domains that are related to the early resignation of instructing doctors, with the aim to develop policy interventions to increase retention of instructing physician in the future. Additionally, future research exploring the reasons behind the resignation decision of instructing doctors is suggested.